(untitled) (Mustansiria Dental Journal, 2018)
Thorough clinical and radiographic examination is necessary to detect, evaluate and diagnose periodontal disease. The aim of present study is to evaluate interdental bone loss in patients with chronic adult periodontitis radiographically. One hundred eighty sites (for maxillary anterior teeth only) were examined for type and severity of alveolar bone loss. The results reveal that 80% of all examined sites had different severity of bone loss. Mild bone loss was more frequent than Moderate or Severe and horizontal more than vertical or angular bone loss. Interdental bone between central and lateral incisors was the most affected site in this study.